Y-4=7x(x-3)

Simple and best practice solution for Y-4=7x(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y-4=7x(x-3) equation:


Simplifying
Y + -4 = 7x(x + -3)

Reorder the terms:
-4 + Y = 7x(x + -3)

Reorder the terms:
-4 + Y = 7x(-3 + x)
-4 + Y = (-3 * 7x + x * 7x)
-4 + Y = (-21x + 7x2)

Solving
-4 + Y = -21x + 7x2

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + Y = -21x + 4 + 7x2

Combine like terms: -4 + 4 = 0
0 + Y = -21x + 4 + 7x2
Y = -21x + 4 + 7x2

Reorder the terms:
Y = 4 + -21x + 7x2

Simplifying
Y = 4 + -21x + 7x2

See similar equations:

| 5+5q=6+4q | | 6(2+-5)+5t=60-1 | | 11-j=2 | | 5+6=9+3 | | 18-13=m | | 2a+4b=30 | | 1.25=0.75r | | -.2t^2-14t=0 | | 25=x+1+2x+3 | | a-10=10 | | 22x-44y= | | 1y+0x=4 | | 0.2x+7.3=6.4 | | (2x+-3)*x=54 | | 9(0)+7x=63 | | 8.65x-6.5=-34.04+13.75x | | 16a=80 | | 3x^3+11x^2-15x+16*3x+2= | | -2=3f-5 | | 4x+2y=6x+12 | | 9(0)+7x^2=63 | | 5(y-6)-16=-11 | | 35*7=(X*7)+(5*7) | | 3=12+k | | 8(8)(-7)(-6)= | | 2a+ab=18 | | x=4x^2-25 | | 22.5x-15=120 | | 6-15-(-9)= | | b-10=15 | | 9x^1+7x^2=63 | | 0.5m+15=0.25m+25 |

Equations solver categories